FAKTOR PENYEBAB ANAK PUTUS SEKOLAH TINGKAT SMA DI DESA BUKIT LIPAI KECAMATAN BATANG CENAKU KABUPATEN INDERAGIRI HULU - Eddy Sugianto; Syamsul Bahri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
In Indonesia, dropout data is relatively high and is in the second position of the country with a high percentage of drop-out rates. The government has not so much been able to cope. Therefore, it is necessary to examine what factors cause the children to drop out of high school education, both in the first year, the second and the last. The research was conducted in Bukit Lipai Village, Batang Cenaku Sub-district, Indragiri Hulu Regency by taking samples of 34 high school students who dropped out of school. The data were analyzed descriptively quantitatively with the result of the research indicated that the characteristics of the families of students who had dropped out of high school education in Bukit Lipai village, Batang Cenaku subdistrict, viewed from the type of parent work were mostly farmers, planters and ranchers, The family decisions to drop out (droup-out) of their children, mostly in the middle of the road or in the second year of the ladder High school education with the main reason for the inability of financing so that on the basis of their own willingness to take the road to drop out of school. Factors that influence or become the main cause of students having dropped out of high school is the economic factor of the family that can not afford, so finally this factor result in -f Other non-economic actors such as the lack of education orand old who lack the willingness and insight for the future of children's education, family environment factors that are less supportive for the creation of an atmosphere of education in the household. All of these factors force directly or indirectly the students to accept the dropout situation in the middle of the road.Keywords: Disconnect High School and Village